The Moderating Role of Emotional Intelligence on the Relationship Between Nurses’ Preparedness to Care for COVID-19 Patients and Their Quality of Work Life - Hanan A. Alkorashy; Aisha F. Basheer; Hanem F. Mohamed (Behavioral Sciences)
Emotional intelligence (EI) is increasingly recognized as a key factor in healthcare, where managing emotions is vital for job satisfaction, productivity, and interpersonal relationships. For nurses, particularly during the COVID-19 pandemic, EI plays a pivotal role in navigating emotional challenges and improving their quality of work life (QoWL). This study examined how EI moderates the relationship between nurses’ preparedness to care for COVID-19 patients and their QoWL. A cross-sectional, correlational design was used, involving 267 nurses from various healthcare settings. Data were collected through the Emotional Intelligence Scale, the Quality of Nursing Work Life survey, and demographic questionnaires. The sample was predominantly female (94.4%), with a mean age of 37.47 years (SD = 8.09) and an average of 8.43 years of experience (SD = 6.33). Most nurses (87.3%) attended COVID-19-related workshops, with 76.4% feeling prepared to care for COVID-19 patients. Emotional intelligence levels were high, with 93.6% of nurses reporting good personal competence and 85.4% reporting good social competence. Descriptive results showed that 71% of nurses perceived their QoWL as good, while 29% rated it as fair. Pearson correlation analysis revealed significant positive correlations between both personal competence (r = 0.33, p < 0.001) and social competence (r = 0.34, p < 0.001) with QoWL, but preparedness to care for COVID-19 patients did not correlate significantly with either EI or QoWL. Hierarchical regression analysis demonstrated that, although nurses’ preparedness alone did not predict QoWL (β = 0.034, p = 0.57), including emotional intelligence as a moderator explains 41% of the variance in QoWL. Both personal (β = 0.578, p < 0.001) and social competence (β = 0.665, p < 0.001) components of EI had significant buffering effects on the relationship between preparedness and QoWL. These findings suggest that fostering EI in nurses can enhance their resilience and improve their work life quality, particularly in high-stress healthcare environments like those experienced during the pandemic.